GLOBAL JET PROPERTIES AT 14-44 GEV CENTER OF MASS-ENERGY IN E+E- ANNIHILATION - Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Fischer, H; Hartmann, H; Hartmann, J; Hilger, E; Jocksch, A; Wedemeyer, R; Foster, B; Martin, A; et al. (Springer-Verlag, 1990)
Jet properties in e+e- annihilation at center of mass energies of 14, 22, 35 and 43.7 GeV were studied with the data collected in the TASSO detector at PETRA, using the same evaluation procedures for all the energies. The total hadronic cross section ratio for the center of mass energy interval 39-47 GeV was determined to be ℛ=4.11±0.05 (stat)±0.18(syst.) at Mathematical expression GeV. Corrected distributions of global shape variables are presented as well as the inclusive charged particle distributions for scaled momentum and transverse momentum. The center of mass energy evolution of the average sphericity, thrust, aplanarity and particle momentum is shown. © 1990 Springer-Verlag.